Semimartingale theory and Complete Markets - Tojtovska, Biljana (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2011)
We are interested in the application of the semimartingale theory in the complete market model consisting of two traded assets. Through the Girsanov theorem the unique martingale measure can be found and the replicating strategy can be constructed. This is discussed on the Black-Scholed market model.
Keywords: Semimartingales, complete market, unique martingale measure, Girsanov theorem, Black-Scholes model